DIFFERENCES IN DIGITAL LITERACY SKILLS OF PROSPECTIVE SCIENCE TEACHER AT MAKASSAR STATE UNIVERSITY BASED ON BATCH - Sitti Saenab; Andi Rahmat Saleh; Adnan Adnan; Annisa Rahma Annabawi; Hasanuddin Hasanuddin (Universitas Negeri Makassar, 2024)
This study aims to determine: (1) the profile of digital literacy skills of prospective science teacher; and (2) whether there are differences in digital literacy skills. This research method is ex-post facto. The population in this study were all prospective science teacher students in Department of Science Education at Universitas Negeri Makassar in the odd semester of the 2022–2023 academic year. The sample was selected using proportionate stratified random sampling techniques, totaling 206 people spread across batches 2019, 2020, 2021, and 2022. The non-test research instrument in the form of a questionnaire consists of 10 statement numbers based on the three dimensions of digital literacy skills proposed by Ng (2012), namely technical, cognitive, and socio-emotional, which are analyzed using descriptive statistical analysis and inferential statistics with one-way ANOVA test analysis. Based on the results of the descriptive statistical analysis of the digital literacy skills of prospective science teacher are in the medium category. Based on the results of an inferential statistical analysis, there are significant differences in the digital literacy skills of prospective science teacher at Universitas Negeri Makassar based on batch.